Is It Possible to Predict an Athlete’s Behavior? The Use of Polar Coordinates to Identify Key Patterns in Taekwondo - Menescardi, Cristina; Falco, Coral; Estevan, Isaac; Ros, Concepción; Morales-Sánchez, Verónica; Hernández-Mendo, Antonio (Frontiers in Psychology, 2019)
Elite sport psychologists help athletes develop planned competition strategies from a technical-tactical perspective, through the observation and analysis of previous performances. The aim of this study was to analyze the behavioral patterns used to score points in the 2012 London Olympic Games, by using a mixed observational methodology through a polar coordinate analysis. This analysis is a representation made into four quadrants of the relationships found between focal behavior [i.e., giving score points, (SC)] and conditioned behaviors considered as key factors in taekwondo, occurring before and after the focal behavior (i.e., retrospective/prospective behavior as indicated for each quadrant respectively): first (activates/activates), second (activates/inhibits), third (inhibits/inhibits) and fourth (inhibits/activates) of two lags (-2, +2). A total of 151 combats, comprising a total of 24,940 actions were analyzed using the Taekwondo Observational Tool, which consists of 24 categories grouped into seven criteria (tactics, techniques, the kicking zone, laterality, the kicking leg, guard, and score). Our analysis confirms significant associations between different types of scoring actions (SC1: to the trunk, SC2: to the trunk with a previous spin, SC3: to the head and SC4: to the head with a previous spin) and a variety of technical-tactical aspects. A total of 50 significant associations were found (29 in males and 21 in females). For male competitors, eight significant associations were found for SC1, six for SC2, four for SC3, and eleven for SC4. For females, twelve significant associations were found for SC1, three for SC2, six for SC3, and no significant association was found for SC4. The observed relationships provide objective data regarding successful behavioral patterns, constituting an important knowledge base for psychologists to train and develop psychological strategies to prepare athletes for future competitions. The identified associations are useful, for instance, in individualizing and personalizing training sessions, including practicing visualization of specific and real situations that occur during competition. The results can also help in planning tactical training by mechanizing and automatizing tactical situations, simplifying and reducing them to a minimal expression. This is done by first by practicing in slow motion and thereafter increasing the velocity and complexity of the situation.